BINAP-copper supported by hydrotalcite as an efficient catalyst for the borrowing hydrogen reaction and dehydrogenation cyclization under water or solvent-free conditions. Issue 11 (8th May 2018) - Xu, Zhaojun; Yu, Xiaoli; Sang, Xinxin; Wang, Dawei
Abstract : A BINAP-Cu system supported by hydrotalcite has been developed and proved to be a highly efficient catalyst for the atom-efficient and green borrowing hydrogen reaction and dehydrogenative cyclization. Abstract : A BINAP-Cu system supported by hydrotalcite has been developed and proved to be a highly efficient catalyst for the atom-efficient and green borrowing hydrogen reaction and dehydrogenative cyclization. This BINAP-Cu complex supported by hydrotalcite is highly air-stable and can be recycled at least five times under solvent-free conditions. Notably, 1-benzyl-2-aryl-1 H -benzo[ d ]imidazole derivatives could be synthesized from alcohols in only one step with water as the solvent for the first time. This provided a much greener and efficient catalytic method towards the synthesis of functionalized amines, ketones and 1-benzyl-2-aryl-1 H -benzo[ d ]imidazole derivatives with high yields under water or solvent-free conditions.